Control of dendrite growth by a magnetic field during directional solidification. (21st April 2016) - Dai, Yanchao; Du, Dafan; Hou, Long; Gagnoud, Annie; Ren, Zhongming; Fautrelle, Yves; Moreau, Rene; Li, Xi
Abstract: In this work, the alignment behavior of three kinds of dendrites (Al3 Ni, α -Al and Al2 Cu dendrites) with a remarkable crystalline anisotropy during directional solidification under an axial magnetic field is studied by the EBSD technology. Experimental results reveal that the magnetic field is capable of tailoring the dendrite alignment during directional solidification. Further, based on the crystalline anisotropy, a method to control the dendrite alignment by adjusting the angle between the magnetic field and the solidification direction is proposed.